Pengembangan Alat Peraga Wayang Berdasarkan Cerita Radin Jambat sebagai Media Pembelajaran Apresiasi Sastra di Sekolah Dasar - Rizki Saputra; Andri Wicaksono; Yulita Dwi Lestari (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
This study aims to develop, test the feasibility, and assess the responses of students and educators toward a wayang puppet prop based on the Radin Jambat story as a medium for literary appreciation education in elementary schools. This study employs the ADDIE model with five stages: Analysis, Design, Development, Implementation, and Evaluation. The wayang puppet prop was validated by subject matter experts and media experts, and the revised version was tested to assess the responses of educators and students. The average validation score from subject matter experts was 85%, and the average validation score from media experts was 93%. Based on these scores from both expert validators, the wayang puppet prop was categorized as “highly feasible.” The response from educators had an average score of 96%, while the response from the small test group of students had an average score of 91%, and the large test group had an average score of 93%. Therefore, the results of the puppet teaching aid development in this study were categorized as “very interesting.” The development of the wayang puppet prop based on the Radin Jambat story as a medium for literary appreciation in elementary schools using the Research and Development (R&D) method leads to the conclusion that the use of the wayang puppet prop in literary appreciation learning is highly suitable and effective as a medium for Indonesian language education.